The role of parents: Addressing elementary school children’s gadget addiction through traditional games - Sintya Nabila; Ayu Maya Damayanti; Yuniar Mujiwati (Journal of Law Science, 2026)
The rapid development of technology—particularly the use of gadgets among children—is increasingly threatening the survival of traditional games, which are beginning to disappear and are no longer played by elementary school-aged children. While the roles of schools, communities, and organizations have been discussed in previous studies, there has been no discussion of the role of parents in preserving traditional games. This study aims to examine the role of parents as both subjects and the “first school” for children at home in guiding and teaching traditional games to their children, as well as the role of parents in fulfilling their obligations as the “first school” for children in the home environment. This study employs a qualitative descriptive approach using in-depth interviews with 18 informants, consisting of parents, children, and teachers. The results of this study indicate that parents in Tenggilisrejo Village are adequately fulfilling their responsibilities in teaching their children some of the traditional games they know, although not very frequently, with obstacles such as a lack of play areas and peers. It is hoped that synergy between parents, teachers or schools, and the community can foster collaboration to ensure that traditional games are preserved and to create a balance amid technological advancements.